CALCULATION OF NONLINEAR VIBRATION ISOLATION SYSTEMS UNDER HARMONIC ACTION - Bakirov, Zhetpisbay; Bakirov, Madi; Tazhenova, Gulzada; Mikhailov, Valentin (Journal of Applied Engineering Science, 2026)
The aim of the study is to develop a methodology for calculating the dynamic characteristics of nonlinear vibration isolators and to evaluate the influence of the type of dissipative forces on the vibration protection efficiency. The paper addresses the calculation of vibration isolators with nonlinear elastic and dissipative properties under harmonic force and kinematic excitations. Using the harmonic linearization method, general expressions were derived for the amplitude-frequency response and the vibration isolation efficiency coefficient. The analysis of these expressions determined the conditions for suppressing large-amplitude vibrations.Specific analytical relationships were obtained for vibration isolators possessing the most common nonlinear elastic characteristics. These include isolators with odd cubic stiffness characteristics, preloaded systems, systems with symmetric linear elastic stops, and systems with a nonlinear elastic element and symmetric rigid stops.It was established that the efficiency of vibration protection systems depends significantly on the type of dissipative forces present in the isolator. Analytical relationships were derived, and the performance of vibration isolators with viscous, dry, and internal friction was analyzed. A comparison of the performance efficiency of vibration isolators with different dissipative characteristics was conducted. The possibility of achieving vibration protection goals by combining different forms of damping is highlighted.
Keywords: vibration isolator, nonlinearity, kinematic action, harmonic linearization, frequency response, vibration isolation coefficient